The interaction between temperature and precipitation on the potential distribution range of Betula ermanii in the alpine treeline ecotone on the Changbai Mountain - Yu Cong; Yongfeng Gu; Wen J. Wang; Lei Wang; Zhenshan Xue; Yingyi Chen; Yinghua Jin; Jiawei Xu; Mai-He Li; Hong S. He; Ming Jiang (Forest Ecosystems)
Alpine treeline ecotones are highly sensitive to climate warming. The low temperature-determined alpine treeline is expected to shift upwards in response to global warming. However, little is known about how temperature interacts with other important factors to influence the distribution range of tree species within and beyond the alpine treeline ecotone. Hence, we used a GF-2 satellite image, along with bioclimatic and topographic variables, to develop an ensemble suitable habitat model based on the species distribution modeling algorithms in Biomod2. We investigated the distribution of suitable habitats for B. ermanii under three climate change scenarios (i.e., low (SSP126), moderate (SSP370) and extreme (SSP585) future emission trajectories) between two consecutive time periods (i.e., current–2055, and 2055–2085). By 2055, the potential distribution range of B. ermanii will expand under all three climate scenarios. The medium and high suitable areas will decline under SSP370 and SSP585 scenarios from 2055 to 2085. Moreover, under the three climate scenarios, the uppermost altitudes of low suitable habitat will rise to 2,329 ​m a.s.l., while the altitudes of medium and high suitable habitats will fall to 2,201 and 2,051 ​m a.s.l. by 2085, respectively. Warming promotes the expansion of B. ermanii distribution range in Changbai Mountain, and this expansion will be modified by precipitation as climate warming continues. This interaction between temperature and precipitation plays a significant role in shaping the potential distribution range of B. ermanii in the alpine treeline ecotone. This study reveals the link between environmental factors, habitat distribution, and species distribution in the alpine treeline ecotone, providing valuable insights into the impacts of climate change on high-elevation vegetation, and contributing to mountain biodiversity conservation and sustainable development.